# Important Questions for Class 12 Chapter 5 - Continuity and Differentiability

Given PDF is the CBSE important questions is all based on the specific guidelines of the CBSE board. Practice the questions thoroughly and get the best marks in exams. Click on the link to download and start practicing the Questions!

Important questions based on NCERT syllabus for Class 12 Chapter 5 - Continuity and Differentiability:

Question 1: Find the value of k, for which f(x) = (√1+kx - √1-kx)/x if -1≤ x<0
(2x+1)/(x-1) if 0≤ x<1
is continuous at x = 0

Solution:
f(x) = (√1+kx - √1-kx)/x if -1≤ x<0
(2x+1)/(x-1) if 0≤ x<1
is continuous at x = 0

Now, f(0) = 2 x 0+ 1/0-1 = 1/-1 = -1

LHL = lim h->0 f(0-h)

= lim h-> 0 (√1 - kh - √1 + kh)/-h

= lim h-> 0 (√1 - kh - √1 + kh)/-h (√1 - kh + √1 + kh/ √1 - kh + √1 + kh)

= lim h-> 0 (1-kh)(1+kh)/-h (√1 - kh + √1 + kh)

Since (a+b)(a-b) = a^2 - b^2

= lim h->0 2kh/ -h (√1 - kh + √1 + kh)

= lim h-> 0 2k/√1 - kh + √1 + kh

= 2k/(1 + 1) = 2k/2 = k

Since f(x) is continuous at x = 0

Therefore, f(0) = LHL => -1 = k

=> k = -1

Question 2: Find the value of a for which the function f is defined as f(x) = asin pi/2(x+1), x<=0
(tan x - sin x)/x^3, x>0
is continuous at x = 0
Solution: Given

f(x) = asin pi/2(x+1), x<=0
(tan x - sin x)/x^3, x>0

Also given that f(x) is continuous at x = 0

Therefore LHL = RHL = f(0)......(1)

Consider LHL = lim x-> 0 a sin pi/2 (x+1)

LHL = lim h->0 a sin pi/2(-h + 1) [put h = 0-h = -h]

= lim h->0 (a sin[pi(-h+1)/2])/(pi(-h+1)/2) * pi(-h+1)/2

Since multiplying numerator and denominator by pi(-h+1)/2

= lim h->0 a pi(-h+1)/2

Since lim x->0 sin x/x = 1

=> LHL = a pi/2

Now consider RHL = lim x -> 0 (tan x - sin x)/x^3

Put x = 0+ h = h, we get

RHL = lim h-> 0 (tan h - sin h)/h^3 = lim h->0 (sin h/cos h - sin h)/h^3

= lim h->0 (sin h - sin h cos h)/h^3 cos h = lim h->0 (sin h(1 - cos h))/h^3 cos h

= lim sin h/h . lim h-> 0 (1-cos h)/h^2. lim h-> 0 1/cos h

= 1 * lim h->0 (1-cos h)/h^2 * 1

since lim h-> 0 sin h/h = 1 and lim h->0 1/cos h = 1/cos 0 = 1/1 = 1

= lim h->0 (1-cos h)/h^2

= lim h->0 (2sin^2 h/2)/h^2 [since 1-cosx = 2sin^2 x/2]

= lim h->0 (2 * sin^2 h/2)/(h^2/4 * 4) = lim h->0 2/4 * lim h->0 (sin^2 h/2)/h^2/4

[since multiply and divided by 4]

= 1/2 * lim h->0 [sin h/2)/(h/2) = 1/2 * 1 * 1

[since lim x->0 sin x/x = 1]

=> RHL = 1/2

Now from equation (1), we have LHL = RHL

Therefore api/2 = 1/2 => api = 1=> a = 1/pi